Inter and Intra Rater Reliability of the 10 Meter Walk Test in the Community Dweller Adults with Spastic Cerebral Palsy - BAHRAMI, Fariba; NOORIZADEHDEHKORDI, Shohreh; DADGOO, Mehdi (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Bahrami F, Noorizadeh Dehkordi SH, Dadgoo M. Inter and Intra Rater Reliability of the 10 Meter Walk Test in the Community Dweller Adults with Spastic Cerebral Palsy. Iran J Child Neurol.Winter 2017; 11(1): 57-64. Abstract Objective We aimed to investigation the intra-rater and inter-raters reliability of the 10 meter walk test (10 MWT) in adults with spastic cerebral palsy (CP). Materials&Methods Thirty ambulatory adults with spastic CP in the summer of 2014 participated (19 men, 11 women; mean age 28 ± 7 yr, range 18- 46 yr). Individuals were non-randomly selected by convenient sampling from the Ra’ad Rehabilitation Goodwill Complex in Tehran, Iran. They had GMFCS levels below IV (I, II, and III). Retest interval for inter-raters study lasted a week. During the tests, participants walked with their maximum speed. Intra class correlation coefficients (ICC) estimated reliability. Results The 10 MWT ICC for intra-rater was 0.98 (95% confidence interval (CI) 0.96-0.99) for participants, and >0.89 in GMFCS subgroups (95% confidence interval (CI) lower bound>0.67). The 10 MWT inter-raters’ ICC was 0.998 (95% confidence interval (CI) 0/996-0/999), and >0.993 in GMFCS subgroups (95% confidence interval (CI) lower bound>0.977). Standard error of the measurement (SEM) values for both studies was small (0.02< SEM< 0.07). Conclusion Excellent intra-rater and inter-raters reliability of the 10 MWT in adults with CP, especially in the moderate motor impairments (GMFCS level III), indicates that this tool can be used in clinics to assess the results of interventions. References 1. Bottos M, Feliciangeli A, Sciuto L, Gericke C, Vianello A. Functional status of adults with cerebral palsy and implications for treatment of children. Dev Med Child Neurol 2001; 43:516-28. 2. Andersson C, Mattsson E. Adults with cerebral palsy: a survey describing problems, needs, and resources, with special emphasis on locomotion. Dev Med Child Neurol 2001; 43:76-82. 3. Murphy KP, Molnar GE, Lankasky K. Medical and Functional Status of Adults with Cerebral Palsy. Dev Med Child Neurol 1995; 37:1075-84. 4. Rapp Jr CE, Torres MM. The adult with cerebral palsy. Arch Family Med 2000; 9:466. 5. Peters DM, Fritz SL, Krotish DE. Assessing the reliability and validity of a shorter walk test compared with the 10-meter walk test for measurements of gait speed in healthy, older adults. J Geriatr Phys Ther 2013; 36:24-30. 6. Fritz S, Lusardi M. White paper:“walking speed: the sixth vital sign”. J Geriatr Phys Ther 2009; 32:2-5. 7. Lord SE, McPherson K, McNaughton HK, Rochester L, Weatherall M. Community ambulation after stroke: how important and obtainable is it and what measures appear predictive? Arch Phys Med Rehabil 2004; 85:234-9. 8. Maki BE. Gait changes in older adults: predictors of falls or indicators of fear. J Am Geriatr Soc 1997; 45:313-20. 9. Tyson S, Connell L. The psychometric properties and clinical utility of measures of walking and mobility in neurological conditions: a systematic review. Clin Rehabil 2009; 23:1018-33. 10. Bohannon RW. Comfortable and maximum walking speed of adults aged 20—79 years: reference values and determinants. Age Ageing 1997; 26:15-9. 11. Judith G, Claudia L, Hubertus VH. Test-retest reliability of gait parameters in children with neurological gait disorders. International Neurorehabilitation Symposium 2013, Science City, ETH Zurich. 12. Watson MJ. Refining the ten-metre walking test for use with neurologically impaired people. Physiotherapy 2002; 88:386-97. 13. van Loo MA, Moseley AM, Bosman JM, de Bie RA, Hassett L. Test-re-test reliability of walking speed, step length and step width measurement after traumatic brain injury: a pilot study. Brain Inj 2004 Oct; 18:1041-8. 14. Steffen T, Seney M. Test-retest reliability and minimal detectable change on balance and ambulation tests, the 36-item short-form health survey, and the unified Parkinson disease rating scale in people with parkinsonism. Phys Ther 2008 Jun; 88:733-46. 15. Pirpiris M, Wilkinson AJ, Rodda J, Nguyen TC, Baker RJ, Nattrass GR, et al. Walking speed in children and young adults with neuromuscular disease: comparison between two assessment methods. J Pediatr Orthop 2003 May-Jun; 23:302-7. 16. Collen FM, Wade DT, Bradshaw CM. Mobility after stroke: reliability of measures of impairment and disability. Int Disability Stud 1990 Jan-Mar; 12 :6-9. 17. Bowden MG, Behrman AL. Step Activity Monitor: accuracy and test-retest reliability in persons with incomplete spinal cord injury. J Rehabil Res Dev 2007; 44:355-62. 18. Scivoletto G, Tamburella F, Laurenza L, Foti C, Ditunno J, molinari M. Validity and Reliability of the 10-m walk test and the 6 min walk test in spinal cord injury patients. Spinal Cord 49:736-40. 19. Thompson P, Beath T, Bell J, Jacobson G, Phair T, Salbach NM, et al. Test-retest reliability of the 10 meter fast walk test and 6 minute walk test in ambulatory school aged children with cerebral palsy. Dev Med Child Neurol 2008;50:370-6. 20. Palisano R, Rosenbaum P, Walter S, Russell D, Wood E, Galuppi B. Development and reliability of a system to classify gross motor function in children with cerebral palsy. Dev Med Child Neurol 1997; 39:214-23. 21. Graham JE, Ostir GV, Fisher SR, Ottenbacher KJ. Assessing walking speed in clinical research: a systematic review. J Eval Clin Pract 2008; 14:552-62. 22. Portney LG, Watkins MP. Foundations of clinical research: applications to practice, FA Davis; 2015 Mar 18. 23. Stratford PW.Getting more from the literature: estimating the standard error of measurement from reliability studies. Physiother Can 2004; 56: 27-30. 24. Bland JM, Altman DG. Statistic and random error in repeated measurements of temporal and distance parameters of gait after stroke. Arch Phys Med Rehabil 1997; 78: 725-29. 25. Wolf S, Catlin P, Gage K, Gurucharri K, et al. Establishing the reliability and validity of measurements of walking time using the Emory Functional Ambulation Profile. Phys ther 1999; 79:1122-33.